L’invention de la mélancolie religieuse ? Quelques réflexions sur un concept pluriel - Lisa Roscioni (Etudes Epistémè)
This article offers some historiographical and methodological reflections on the evolution of the notion of religious melancholy back from its “invention” in 1621, true or alleged it may be, by Robert Burton with his The Anatomy of Melancholy. According to Burton, melancholy may be caused not only by a humoral imbalance but also by moral and social causes. In other conceptual and confessional areas, the idea that melancholy contains in itself a principle of rebellion and disorder, which is performed not only by the single individual – as an expression of protest, inability or unwillingness of the subject to adapt to social rules – but also collectively, – to designate a contagious social disease –, emerges throughout the seventeenth century. In both Catholic and Protestant spheres, many lexical recurrences show the use of this term in its pejorative and polemical meaning in order to stigmatize the severe distance between individuals, groups or peoples from social and religious values, and to undermine its subversive potential.